ANALISIS EFEKTIVITAS RETRIBUSI DAN PAJAK DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MAGELANG TAHUN 2016-2019 - Kintan Arvina Damayanti; Ayunda Putri Nilasari (Transpublika Publisher, 2022)
The objective of this study to investigate and assess the efficacy of local taxes and punishments in boosting the Regional Original Income (PAD) in Magelang Regency. This descriptive study takes a quantitative approach to research, therefore it is a quantitative study. We make use of secondary data that includes information on plans/targets as well as actual local tax revenues, regional levies, and Regional Original Income (PAD). In addition to primary data, secondary data collected by BPPKAD Magelang Regency was used in this study. This is accomplished by measuring and analyzing the efficacy of local and regional taxes on Regional Original Income (PAD). Magelang Regency's local taxes, regional levies, and regional original income (PAD) are the primary focus of this analysis. This research shows that the regional tax share of regional original income (PAD) is, on average, 111.63 percent efficient, making regional taxes very efficient according to the criteria used to classify regional tax efficiency. The regional levy component on Regional Original Income (PAD) has an efficiency of, on average, 78.76% between 2016 and 2019, according to the classification of regional levy effectiveness criteria.